Pembatalan Sepihak Rencana Perkawinan dalam Perspektif Asas Itikad Baik Pra-Kontraktual - Faris Ihza Syahputra; Anjar Sri Ciptorukmi Nugraheni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The unilateral cancellation of marriage plans has increasingly raised legal concerns, particularly regarding the absence of a clear legal basis for liability in Indonesian positive law during the pre-marital phase. This study aims to examine the legal qualification of such unilateral cancellation as a breach of contract through the interpretation of the principle of good faith in the pre-contractual phase. The research employs a normative legal method with prescriptive and applied characteristics, utilizing statutory and conceptual approaches. Legal materials consist of primary and secondary sources analyzed through deductive reasoning using a syllogistic method. The findings reveal that although marriage plans do not constitute a legally binding contract, the existence of serious commitments and preparatory actions, including public announcements, creates a legitimate expectation that obliges the parties to act in good faith. The unilateral withdrawal from such arrangements may therefore be interpreted as a violation of pre-contractual good faith, giving rise to legal liability. From a modern contract law perspective, this conduct can be qualified as a form of breach of obligation within the framework of culpa in contrahendo, even in the absence of a formally concluded agreement. The study concludes that the application of the principle of good faith in the pre-contractual phase provides a more comprehensive legal basis for protecting the injured party and offers an alternative framework beyond traditional tort-based approaches.